Characteristics of inhomogeneous lower extremity growth and development in early childhood: a cross-sectional study - Sudarat Apibantaweesakul; Shiho Omura; Weihuang Qi; Hiroto Shiotani; Pavlos E. Evangelidis; Natsuki Sado; Fumiko Tanaka; Yasuo Kawakami (BMC, 2021)
Abstract Background Early childhood is a transferring stage between the two accelerated growth periods (infant and adolescent). Body dimensions are related to physical growth and development. The purpose of this study was to investigate physical growth in terms of anthropometry, muscle growth of the lower extremity, and functional development over early childhood. Methods A cross-sectional study was carried out on 29 preschool children (PS: 3-5 years), 21 school children (SC: 6-8 years), and 22 adults (AD: 20-35 years). Lower extremity characteristics (segmental dimensions, muscle and adipose tissue thicknesses of the thigh and lower leg), and voluntary joint torque (knee and ankle) were measured. Correlations between parameters and group comparisons were performed. Results All the parameters except for body mass index (BMI) and subcutaneous adipose tissue thickness were correlated with age for PS and SC combined (r = 0.479-0.920, p < 0.01). Relative thigh and shank lengths to body height were greatest in AD and smallest in PS (p < 0.05) but the relative foot dimensions were significantly larger in PS and SC than in AD (p < 0.05). Relative subcutaneous adipose tissue thickness was largest in PS and lowest in AD. Muscle thickness and the muscle volume measure (estimated from muscle thickness and limb length) were significantly larger in older age groups (p < 0.05). All groups showed comparable muscle thickness when normalized to limb length. Joint torque normalized to estimated muscle volume was greatest for AD, followed by SC and PS (p < 0.05). Conclusions Relative lower extremity lengths increase with age, except for the foot dimensions. Muscle size increases with age in proportion to the limb length, while relative adiposity decreases. Torque-producing capacity is highly variable in children and rapidly develops toward adulthood. This cross-sectional study suggests that children are not a small scale version of adults, neither morphologically nor functionally.